Availability, affordability, and associated factors of essential medicines in primary health care facilities of the wolaita region, southern Ethiopia: implication for access, a cross-sectional study, 2022 - Adale, AtsedeTenna (Research in Health Services & Regions, 2025)
Introduction Access to essential medicines is fundamental to achieving universal health coverage. According to WHO, these medicines should be consistently available and affordable. However, in many low- and middle-income countries, health facilities experience frequent stockouts and high prices, limiting access and affordability. Such barriers reduce adherence, increase out-of-pocket spending, and compromise health outcomes. Assessing availability and affordability in primary health care facilities is therefore crucial to inform policy and promote equitable access. Objectives To assess the availability and affordability of essential medicines and associated factors in Wolaita region, Ethiopia, 2022. Methods A facility-based cross-sectional study was conducted from February 1–30, 2022. Thirty public health facilities were selected, six from each of five districts. Sample size was determined using a single population proportion formula. Data were collected through patient exit interviews, entered into EpiData 3.1, and analyzed in SPSS version 25. Multivariable logistic regression was employed to identify factors associated with affordability. Results Of 601 patients, 98% participated. The average availability of 26 selected core essential medicines was 56.53%. Among patients, 58.1% reported prescribed medicines as unaffordable. Factors significantly associated with affordability included level of health facility [AOR (95% CI) = 3.450 (2.275–5.231)], health status [AOR = 1.807 (1.027–3.179)], educational status [AOR = 3.413 (1.363–8.548)], and place of residence [AOR = 1.596 (1.019–2.551)]. Conclusion Essential medicine availability was low across facilities. Many patients were unable to obtain prescribed drugs due to unavailability and unaffordability. District and zonal health offices should ensure timely replenishment to strengthen access.